2007
DOI: 10.1146/annurev.pharmtox.46.120604.141046
|View full text |Cite
|
Sign up to set email alerts
|

Cell Survival Responses to Environmental Stresses Via the Keap1-Nrf2-ARE Pathway

Abstract: Keap1-Nrf2-ARE signaling plays a significant role in protecting cells from endogenous and exogenous stresses. The development of Nrf2 knockout mice has provided key insights into the toxicological importance of this pathway. These mice are more sensitive to the hepatic, pulmonary, ovarian, and neurotoxic consequences of acute exposures to environmental agents and drugs, inflammatory stresses, as well as chronic exposures to cigarette smoke and other carcinogens. Under quiescent conditions, the transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
2,501
3
24

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,153 publications
(2,583 citation statements)
references
References 111 publications
55
2,501
3
24
Order By: Relevance
“…3A). The canonical ARE typically harbors a consensus sequence of 5′ TGAC-nnn-GC-3′ that could be specifically recognized by Nrf2, and the binding to ARE by Nrf2 is fundamentally involved in anti-oxidative stress responses [3,53]. To interrogate the binding of Nrf2 to the ARE within its promoter region, the ChIP assay in MEL cells was performed.…”
Section: Nrf2 Transcriptionally Drives Mir-214 Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…3A). The canonical ARE typically harbors a consensus sequence of 5′ TGAC-nnn-GC-3′ that could be specifically recognized by Nrf2, and the binding to ARE by Nrf2 is fundamentally involved in anti-oxidative stress responses [3,53]. To interrogate the binding of Nrf2 to the ARE within its promoter region, the ChIP assay in MEL cells was performed.…”
Section: Nrf2 Transcriptionally Drives Mir-214 Expressionmentioning
confidence: 99%
“…A considerable number of studies have demonstrated that Nrf2 signaling protects cells from many hazardous stimuli, such as radiation, invading pathogens and foreign chemicals (e.g. drugs through therapeutic interventions and environmental toxicants) [3][4][5]. Nrf2 directly targets a battery of roughly 250 genes responsible for a wide array of cellular antioxidant responses and detoxification processes, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, factors involved in ARE activation are highly homologous, thereby allowing cross-species activation of ARE-containing vectors. 35 It is therefore unlikely that AREs from the mouse gene would be functionally impaired in human cells thereby explaining the differences in activity. Conversely, vectors having ARE sequences derived from human genes are likely to be functional in cells derived form other species allowing the use of these in animal models of CVD.…”
Section: Oxidative Stress-inducible Vectorsmentioning
confidence: 99%
“…Activation of NRF2 is a well-known adaptive response to environmental and endogenous stresses. Recent studies uncovered that NRF2 influences a wide range of physiologic and pathologic processes such as inflammation, carcinogenesis, chronic obstructive pulmonary disease, obesity, and neurodegeneration [9].…”
Section: Introductionmentioning
confidence: 99%